Exploration of Financial Knowledge, AI Integration, Human Capital, Digital Marketing, and SME Competitiveness - Rina Amelia; Siti Fatimah; Isna Wati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research aims to investigate the multifaceted components influencing the competitive edge of Small and Medium Enterprises (SMEs). The research model integrates financial knowledge, AI integration, human capital, and digital marketing to explore their collective impact on SME competitiveness. Through purposive sampling, SMEs across diverse sectors will be selected for in-depth interviews and focus group discussions. Data analysis will employ thematic analysis techniques to derive rich insights from qualitative data. The study anticipates uncovering nuanced relationships between the aforementioned variables and SME competitiveness. Findings will contribute to enhancing understanding of the intricate dynamics shaping SME competitiveness and inform strategic interventions to bolster their competitive edge in the market landscape.